Thom polynomials of Morin singularities - Berczi, G; Szenes, A (2012)
We prove a formula for Thom polynomials of A d singularities in any codimension. We use a combination of the test-curve model of Porteous, and the localization methods in equivariant cohomology. Our formulas are independent of the codimension, and are computationally effective up to d = 6.